Using rock music as a teaching-learning tool (2008)
The use of rock music in English teaching-learning contexts gains relevance as many of the people involved in them listen to this kind of music. The integration of rock music into language learning can be done if the music is treated as class material, taking into account that it requires previous and careful preparation. In this article I will show my experience working with two students in classes in which the materials were based on the lyrics of rock songs. The motivations, reflections, information collected and findings made during the process compose the following article in which rock music and learning are the central characters of a research study carried out with two adult students. Key words: Rock music in ELT, music as authentic material, teaching-learning tools El uso de la música rock en el contexto de la enseñanza y aprendizaje del inglés cobra relevancia dado que muchas personas involucradas en el proceso escuchan esta clase de música. La integración de este tipo de material en la enseñanza de lenguas es posible si la música se presenta como material de clase, teniendo en cuenta que requiere preparación previa y cuidadosa. En este artículo deseo compartir la experiencia de trabajar con dos estudiantes en clases cuyos materiales se basaron principalmente en letras de canciones de rock. Las motivaciones, reflexiones, información recolectada y hallazgos durante el proceso se incluyen en este artículo en el cual la música rock y el aprendizaje son los protagonistas principales de un estudio realizado con dos adultos. Palabras clave: Música rock en la enseñanza del inglés, música como material auténtico, herramientas para la enseñanza-aprendizaje